ORGANIC MATTER AND MINERAL BANANA STEMS SILASE WITH A VARIETY OF BUTTERFLY PEA(Clitoria ternatea) LEVELS - D, Kartikasari; Mahardika, I G.; Suryani, N. N. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
This study aims to determine the level of addition of butterfly pea in terms of organic matter and minerals. This research was conducted at Sesetan Farm, Faculty of Animal Husbandry, Udayana University, Jl. Raya Sesetan, Markisa Alley, Denpasar. Organic material testing was carried out at the Laboratory of Nutrition and Animal Feed at the Faculty of Animal Husbandry, Udayana University and mineral testing was carried out at the Analytical laboratory of Udayana University. The research design used was a completely randomized design (CRD) with 4 treatments and 4 replications. Treatment A (65% banana stem + 30% pollar + 5% (molasis + EM4)), B (55% banana stem + 10% C. ternatea + 30% pollar + 5% (molasis + EM4)), C (45 % banana stem + 20% C. ternatea + 30% pollar + 5% (molasis + EM4)), D (35% banana stem + 30% C. ternatea + 30% pollar + 5% (molasis + EM4)). The research variables are organic matter and minerals (Ca, P, and Zn). The results showed that the percentage of organic matter had significantly increased (P <0.05). The minerals Ca, P, and Zn increased and were highest in treatment C respectively 32.58 ml / L, 0.75% and 19.26 mg / kg. From the results of this study it can be concluded that the addition of clitoria ternatea to banana stem silage can increase the content of organic matter and minerals (Ca, P, and Zn). The addition of 30% clitoria ternatea produces the highest organic matter, while the addition of 20% clitoria ternatea produces the highest minerals (Ca, P, and Zn) in banana stem silage.  Keywords : banana stems, organic matter, clitoria ternatea , minerals Ca, P, Zn